Sensory marketing, consumer psychology and the future of branding within the Airline industry: Singapore Airlines - Warren, Andrew (The IIE, 2017)
In this postmodern world, the marketplace is concentrated with many forms of media with the average person being exposed to 4000+ every day. Brands have been forced to innovate and create new and improved forms of adding value to consumers lives. As Martin Lindstrom states “up to 90% of consumer behaviour/buying decisions are subconscious which leaves marketers to target the remainder 10%”. It’s time to change marketing tactics and attempt to break the clutter via sensory marketing. Targeting the subconscious could be the key to future of effective branding. Taking a step back and studying the marketplace I was able to single out the Airline Industry as the perfect place to start. Incorporating the five components of sensory marketing (Touch, Taste, Sight, Sound, Smell) I will be able to highlight aspects of sensory marketing that’s making a difference. Singapore Airlines stood out as the powerhouse of the sensory experience and so I developed an integrated brand identity and sensory analysis to investigate the relationship between the two. Sensory marketing within Singapore Airlines is a major focal point and transports the brand value into tangible experiences. The future of which can only be developed even more. Various research methods were put into play with in-depth interviews being at the heart of the study. This revealed many interesting aspects surrounding the development and effectiveness of sensory marketing, not only within the airline industry but in the marketplace as a whole.
Keywords: Brands; Branding; Airline Industry; Consumer Behaviour; Marketing; Brand Identity; Sensory Marketing; Brand Innovation